Upaya Meningkatkan Literasi Guna Meminimalkan Masalah Kurangnya Minat Baca pada Anak - Hassa Nia Harahap; Randa Putra Kasea Sinaga (Yayasan Literasi Sains Indonesia, 2023)
Indonesian language is the nation’s unifying language. The language used as the official language of the Indonesian nation and is a communication tool used by Indonesian people. With regard to the Indonesian language, it is very related to literacy. Literacy is the ability to read and write or also known as literacy (Heru Susanto, 2016). Literacy is also interpreted as an education or learning (Muhammad Muiz, n.d.). This literacy is especially important for children in order to minimize the problem of a lack of interest in reading at a child’s productive age. Therefore the purpose of this writing is to seek to increase literacy in order to minimize the problem of a lack of interest in reading in children by using the Micro Intervention stage with the Case Work method which has several stages namely: (1) Engagement intake contact, (2) Assessment, (3) Planning , (4) Intervention, (5) Monitoring, (6) Evaluation, (7) Termination. Elementary school was chosen as a means of instilling literacy because it is expected to literacy habit from an early age, students can acquire literacy habits as a provision for face the future. That will be obtained from the results obtained from this activity is the ability, progress, and willingness to learn and develop literacy in order to increase interest in reading in children, especially children in the productive age of learning.